2005
DOI: 10.1038/sj.bjc.6602743
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 as a potential marker for the malignancy of colorectal cancer

Abstract: To test the hypothesis that plasminogen activator inhibitor-1 (PAI-1) may serve as a candidate marker for the malignancy of colorectal cancer (CRC), we performed a quantitative RT -PCR for PAI-1 gene and evaluated the possible relationship between PAI-1 gene expression levels and clinicopathological findings in CRC. A significant increase in PAI-1 expression scores was observed in lymph node metastasis-positive CRCs (2.1970.43) compared to negative ones (0.3570.42) (P ¼ 0.0037) as well as in distant metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 27 publications
3
40
1
Order By: Relevance
“…An increased uPA, uPAR, PAI 1 and PAI 2 expression in tumor tissue was confirmed in a number of tumors, such as breast, ovarian, kidney and stomach [26][27][28][29][30][31][32] and it is certain that these factors play an important role in tumor invasiveness and metastasizing.…”
Section: Discussionmentioning
confidence: 99%
“…An increased uPA, uPAR, PAI 1 and PAI 2 expression in tumor tissue was confirmed in a number of tumors, such as breast, ovarian, kidney and stomach [26][27][28][29][30][31][32] and it is certain that these factors play an important role in tumor invasiveness and metastasizing.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PAI-1 has been found in many obesity-related types of cancer and is associated with the progression of breast, endometrial, colorectal, thyroid, renal, and prostate cancer (97)(98)(99)(100)(101)(102). In addition to autocrine production by tumor cells, systemic levels of PAI-1 (e.g., produced by immune cells or adipocytes in obesity) appear to be essential for its tumor-promoting effects, though level dependent (103).…”
Section: Adipokinesmentioning
confidence: 99%
“…Finally, we demonstrated that PAI-1 expression was significantly correlated with a poor prognosis in esophageal squamous cell carcinoma and colorectal cancer. (24,25) These results prompted us to examine the PAI-1 expression level in other cancers, especially in gastric cancer.To test the hypothesis that PAI-1 may serve as a candidate marker for malignancy in gastric cancer, we carried out a quantitative RT-PCR and evaluated the relationship between PAI-1 gene expression levels and clinicopathological findings in gastric cancer. …”
mentioning
confidence: 99%